IMPLEMENTASI PRODUK SMART CITY MELALUI APLIKASI REAKSI ATAS BERITA WARGA (RABEG) DALAM KETERBUKAAN INFORMASI PUBLIK BERDASARKAN PERATURAN WALIKOTA SERANG NOMOR 36 TAHUN 2018 - Ita Ismawana; Abu Nawas; Agus Prihartono (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Efforts to advance the smart city in Serang City involve all Regional Apparatus Organizations (OPD), with the Serang City Communication and Information Agency (Diskominfo) as the department overseeing the smart city program in Serang City. One of the implementations of the smart city program is the RABEG application. The researcher aims to examine this topic through a study entitled "Implementation of Smart City Products Through the RABEG Application Based on Serang Mayor Regulation Number 36 of 2018 in Serang City, Banten." The purpose of this study is to determine the implementation of smart city products through the RABEG (Reaksi Atas Berita Warga or Citizen News Response) application and the inhibiting factors. This research is expected to provide theoretical, practical, and academic benefits. The researcher employs an empirical juridical research method with a qualitative descriptive approach. Data sources and collection techniques use secondary data. The research location is the Serang City Communication and Information Agency. The results of the study indicate that the implications of the RABEG application are highly positive for the people of Serang City, serving as a platform for both the community and the government, while also encompassing the quality of public services and ease of access for the public in conveying their aspirations. The positive implications of the RABEG application include time and cost efficiency, transparency and accountability, as well as ease of access and increased community participation. The Serang City Government, as the capital of Banten Province, is also striving to implement the smart city concept and has begun to release supporting application products as part of smart city implementation, with the RABEG application being one of Serang City's smart city products. However, the implementation faces several obstacles, including slow-responsive OPD, internet network issues, and human resource constraints.